Design of active microwave absorbers - Zhou, Kailun (2017)
At first, a non-Foster active absorber with ultra wideband and extremely low profile is verified in the thesis, which can effectively break the Rozanov limit for passive absorbers. The design concept is explained through the transmission line theory while the interpretation of the non-Foster matching process is also provided. We also optimize the substrate thickness of absorber. The simulated results show that an ultra-thin absorber with one-decade bandwidth is realized, where the thickness is only 1/100 0 at frequency of 100 MHz. After that, the non-Foster active absorber is designed to realize the function of dual-polarization by stacking another active layer perpendicular to the original one. Then the absorber is improved for practical implementation. The dual-polarized absorber is realized by putting all the active elements on the bottom of the absorber below the ground while the strip line on the top is connected with the active elements by using four copper cylinders. Through the designed frequency-varying inductance, the absorber can also achieve an extreme wide bandwidth. In the last design, we focus on the potential of magnetic material and explore the influence to further decrease the thickness of the dual-polarized non-Foster active absorber. The parameter of magnetic material is calculated and also frequency-varying. By employing the magnetic material, the simulated results also show a positive effect. This thesis provides the main concept to design an ultra wideband absorber by using the non-Foster matching condition. The way of realizing dual-polarization and optimizing the thickness is suggested.